Deconstruction of Islamic Scientific Authority: A Phenomenological Study on the Impact of Authentication Reduction Toward Pseudo Literacy Among Islamic University - Rabiha Maya Adiera; Eliwatis Eliwatis; Syahrur Ramli; Silfia Hanani; Salmiwati Salmiwati; Zulfani Sesmiarni; Nadia Zakia (JPI: Jurnal Pustaka Indonesia, 2026)
The rapid integration of Artificial Intelligence (AI) in Islamic Higher Education Institutions (PTAI) has sparked a significant shift in how students engage with religious knowledge. This study investigates the deconstruction of Islamic scientific authority, focusing on the impact of authentication reduction toward "pseudo-literacy" among Islamic Religious Education (PAI) students at UIN Mahmud Yunus Batusangkar. Utilizing a phenomenological approach combined with quantitative empirical data, this research explores the lived experiences of the 2023-2025 cohorts the "AI-native" generation. Findings indicate a critical trend of "epistemic dislocation," where students increasingly bypass traditional verification processes (isnad and tabayyun) in favor of algorithmic convenience. Statistical analysis reveals that authentication reduction has a significant positive influence on the rise of pseudo-literacy, with 82% of respondents showing high dependency on AI-generated content without cross-referencing primary classical texts (turats). Qualitative interviews further highlight "competence illusions," where students produce high volumes of text but lack deep conceptual understanding, leading to "cognitive atrophy." This phenomenon poses a serious theological and pedagogical threat, potentially producing a generation of religious educators severed from their scholarly roots. This study recommends a radical pedagogical reorientation through an "AI-Literacy with Sanad" framework, positioning AI as a supportive tool rather than a substitute for intellectual rigor. Ultimately, reclaiming scholarly authority requires reintegrating the ethics of adab and strict authentication into the digital-era curriculum to safeguard the integrity of Islamic scientific traditions.